Flipped Learning Berbasis Pedagogi Ignasian pada Kuliah Perjanjian Baru Fakultas Teologi Universitas Sanata Dharma - Timmerman, Bobby Octavianus; Dirgaprimawan, Bernadus; Lelono, Martinus Joko (Sanata Dharma University, 2024)
Responding to the needs of students in this digital era, the utilization of educational technology must be welcomed and used properly in the classroom. Flipped Learning (FL) is one of them. The implementation of flipped-learning by involving audio-visual content and the utilization of digital media will certainly help students to further absorb learning materials. Using devices, students can access lecture materials before the meeting. Sanata Dharma University also uses a Learning Management System (LMS) that can be optimized to support this flipped-learning. This paper aims to discuss the application of FL in “Introduction to New Testament” courses at the Faculty of Theology and the evaluation of this method. The method used is participatory observation of the author as lecturers involved in this FL-based learning and also literature study related to the basic concepts of FL to help deliver material to students in this digital era. The results showed that the application of this FL based on Ignatian pedagogy helped students to have an intellectual, participatory, and practical learning experience.